2021
DOI: 10.1101/2021.03.17.435892
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Style Transfer Using Generative Adversarial Networks for Multi-Site MRI Harmonization

Abstract: Large data initiatives and high-powered brain imaging analyses require the pooling of MR images acquired across multiple scanners, often using different protocols. Prospective cross-site harmonization often involves the use of a phantom or traveling subjects. However, as more datasets are becoming publicly available, there is a growing need for retrospective harmonization, pooling data from sites not originally coordinated together. Several retrospective harmonization techniques have shown promise in removing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 17 publications
(13 reference statements)
0
26
0
Order By: Relevance
“…Future work will also assess the added value of additional imaging protocols, such as quantitative MRI, 25 which may boost classification performance. We plan to test the added value of MRI data harmonization approaches based on generative adversarial networks, such as CycleGANs 26 or CALAMITI, which can make MRI data from different scanners or protocols more comparable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future work will also assess the added value of additional imaging protocols, such as quantitative MRI, 25 which may boost classification performance. We plan to test the added value of MRI data harmonization approaches based on generative adversarial networks, such as CycleGANs 26 or CALAMITI, which can make MRI data from different scanners or protocols more comparable.…”
Section: Discussionmentioning
confidence: 99%
“…We plan to perform additional experiments with 2D variants as this might also help to reduce overfitting issues for low data problems such as the tasks defined here. We are also working on creating activation maps as a way to improve interpretability of the model's prediction, and plan to test the added value of MRI data harmonization approaches based on generative adversarial networks, such as CycleGANs 26 or CALAMITI, 27 which can make MRI data from different scanners or protocols more comparable.…”
Section: Discussion and Future Workmentioning
confidence: 99%
“…There has been a recent explosion in methods that apply machine learning and other advanced multivariate techniques to tackle harmonization. Machine learning methods, including deep-learning approaches, have been developed in recent years to harmonize neuroimaging data without a priori hypotheses about data distributions (Blumberg et al, 2019; Dinsdale et al, 2021; Liu et al, 2021; Moyer et al, 2020; Ning et al, 2020; Tax et al, 2019). A universal machine learning method that is capable of harmonizing data across sites, time, and imaging modalities may enhance our ability to use both existing data and yet to be acquired data (Zuo et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The qualitative results showed that their methods performed better however, in the quantitative evaluation (peak signal to noise ratio and structure similarity index), supervised learning performed better than unsupervised learning. A similar study by Liu et al [ 115 ] was carried out to harmonize MRI images from multiple arbitrary sites using a style transferable GAN. They treated harmonization as a style transfer problem and proved that their model applied to unseen images provided there was enough data available from multiple sites for training purposes.…”
Section: Image Domain Harmonizationmentioning
confidence: 99%